2020
DOI: 10.21147/j.issn.1000-9604.2020.05.02
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 promotes cell aggressiveness and paclitaxel resistance through NF-κB/STAT3 signalling pathway in breast cancer cells

Abstract: Objective Although T-cell immunoglobulin and mucin-domain containing molecule-3 (Tim-3) has been recognized as a promising target for cancer immunotherapy, its exact role in breast cancer has not been fully elucidated. Methods Tim-3 gene expression in breast cancer and its prognostic significance were analyzed. Associated mechanisms were then explored in vitro by establishing Tim-3-overexpressing breast cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Moreover, further TCGA data (n=9491 cases) also confirmed a significant relationship between TIM-3 expression and poor OS, and no relationship between TIM-3 expression and DFS in cancer. TIM-3 may have a function in promoting tumor cell proliferation, migration, and invasion ( 66 , 67 ). TIM-3 facilitates the initiation of tumor and tumor-promoting activities ( 66 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, further TCGA data (n=9491 cases) also confirmed a significant relationship between TIM-3 expression and poor OS, and no relationship between TIM-3 expression and DFS in cancer. TIM-3 may have a function in promoting tumor cell proliferation, migration, and invasion ( 66 , 67 ). TIM-3 facilitates the initiation of tumor and tumor-promoting activities ( 66 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…TIM-3 may have a function in promoting tumor cell proliferation, migration, and invasion ( 66 , 67 ). TIM-3 facilitates the initiation of tumor and tumor-promoting activities ( 66 , 68 ). The interactions between TIM-3 and its ligands inhibit Th1 and Th17 responses and NK cell-mediated cytotoxicity, resulting in immune tolerance ( 68 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The STAT3 and NF-κB signaling pathways are two vital intracellular pathways that serve key roles in modulating cell differentiation, proliferation, migration and metabolism (37,38). These pathways are frequently overactivated in various types of cancer, including colorectal, non-small lung and breast cancer, and have been reported to contribute to tumor progression and drug resistance (39)(40)(41). Previous studies have demonstrated that the STAT3 and NF-κB pathways are aberrantly activated during EScc development (17,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Tim-3 overexpression in breast cancer cells promotes cell proliferation, migration, invasion, and tumor-associated tubal formation and enhances chemoresistance to paclitaxel by activating the NF-κB/STAT3 pathway and its downstream genes (cyclin D1, matrix metalloproteinase-1, vascular endothelial growth factor, and E-cadherin). Tim-3 also deteriorates tight junctions by downregulating zona occludens (ZO)-2, ZO-1, and occludin, which further accelerates tumor progression ( 54 ). Another study supported the aforementioned findings by reporting that downregulation of Tim-3 in breast cancer cells inhibited their proliferation, migration, and invasion and promoted their apoptosis ( 20 ).…”
Section: The Role Of Tim-3 Expression On Tumor Cells In Breast Cancermentioning
confidence: 99%